A Transaction Cost-Benefit for the Bottom of the Pyramid Market - Verma, Pranay (Indian Journal of Marketing, 2025)
Purpose : Transaction cost benefit is the prime reason for the adoption of technology by the bottom of the pyramid who survive on agriculture. This article empirically tested perceived economic well-being (PEWB) and conspicuous consumption (CC) for being the antecedents of transaction cost benefit as discerned by the bottom of the pyramid (BoP) section. Methodology : Data were collected from 329 respondents by a two-stage stratified sampling procedure from rural Indian farmers using a structured survey instrument. In the first stage, the measurement model was examined for its reliability and validity, while in the second stage, the strength and direction of the hypothesized paths were investigated through the structural model. The relationships were subsequently checked for the moderation effects of income and gender. Findings : This study affirmed that CC and PEWB established transaction cost benefits. Moreover, income and gender moderated the PEWB–CC relationship, resulting in important implications for the service providers. Practical Implications : The BoP segment also wants to show off or consume conspicuously. If they are able to achieve it, they sense a benefit. Any perceived economic or non-economic benefit with the use of a product/service augurs cost benefit for this segment. Originality : Through this research, the author identified the interplay of CC and PEWB, which leads to transaction cost benefits. It can be used as a measure to gauge the financial inclusion of bottom-of-the-pyramid farmers in developing countries.